2005
DOI: 10.2337/diacare.28.11.2662
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Diabetes on Employment and Work Productivity

Abstract: OBJECTIVE -The purpose of this study was to longitudinally examine the effect of diabetes on labor market outcomes.RESEARCH DESIGN AND METHODS -Using secondary data from the first two waves (1992 and 1994) of the Health and Retirement Study, we identified 7,055 employed respondents (51-61 years of age), 490 of whom reported having diabetes in wave 1. We estimated the effect of diabetes in wave 1 on the probability of working in wave 2 using probit regression. For those working in wave 2, we modeled the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
192
2
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(223 citation statements)
references
References 29 publications
17
192
2
12
Order By: Relevance
“…Previous studies from Canada and the USA have indicated differences in earnings, but did not consider type 1 diabetes in particular, nor did they control for duration of diabetes [1][2][3][4][5][6][7][8][9][10][11][12]. In this study we have established more firmly, first, that the differences in earnings were in fact induced by the onset of diabetes using the before-after design and individual-level longitudinal annual data.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Previous studies from Canada and the USA have indicated differences in earnings, but did not consider type 1 diabetes in particular, nor did they control for duration of diabetes [1][2][3][4][5][6][7][8][9][10][11][12]. In this study we have established more firmly, first, that the differences in earnings were in fact induced by the onset of diabetes using the before-after design and individual-level longitudinal annual data.…”
Section: Discussionmentioning
confidence: 74%
“…The scarce literature on consequences of type 1 diabetes on earnings, education and participation in the labour market may be explained by the difficulties in obtaining data to confirm a causal relationship. A few published studies have described labour-market outcomes for persons with diabetes of varying duration, relying on cross-sectional data and on self-reporting of diabetes in surveys [1][2][3][4][5][6][7][8][9][10][11][12]. Cross-sectional data may show associations, but are not sufficient for identifying causal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Unless concerted efforts are undertaken, the economic burden of diabetes will continue to rise by contributing to work loss through absenteeism and health-related work limitations in the workplace. 5 In addition, our findings suggest that disparities of missed workdays based on gender will assist policy makers to consider further efforts to improve women's health, thereby reducing the economic burden to women associated with missed workdays due to injury/illness. Key strategies to reduce missed workdays in people with diabetes include improving the clinical care of diabetes, increasing medication adherence, reducing complications and treating comorbid mental illnesses such as depression.…”
Section: Discussionmentioning
confidence: 99%
“…5,9,26 The economic burden associated with diabetes is likely to increase as diabetes becomes more prevalent. 5 With rising prevalence of diabetes in the US, cost of missed workdays will continue to rise, and quantifying the incremental and aggregate cost of missed workdays is believed to be important to employers, to estimate potential cost savings of minimizing job absenteeism, along with interventions to reduce diabetes. Unless concerted efforts are undertaken, the economic burden of diabetes will continue to rise by contributing to work loss through absenteeism and health-related work limitations in the workplace.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation